Social Network Site Usage Among Adolescents: Effects on Mental and Physical Well-being - Guðrún Alma Einarsdóttir 1988- (2015)
Social network sites have increased substantially in popularity in our society where the majority of users are adolescents. Social network sites are various web-based platforms that enable individuals to create profiles, interact with friends and family, share photos and information, play games, and chat through instant messaging. Whereas adolescence is a vulnerable period to susceptibility to various social influences it is important to examine the effects social network sites may have. The study consisted of archival data from the Icelandic Centre for Social Research and Analysis (ICSRA), Youth in Iceland 2013. Participants of the current study were a random sample of 2.070 adolescents from a population of 11.116 Icelandic high school students. The majority of participants were from the age 16 to 19 years old. The main results of the study indicated that adolescents who use social network sites more frequently are adversely affected by the usage (both mental and physical well-being) as well as having indirect effects on depression through self-esteem. Notkun samfélagsmiðla hefur aukist verulega í vinsældum í okkar samfélagi þar sem meirihluti notenda eru unglingar. Samfélagsmiðlar eru ýmis vettvangur á internetinu þar sem einstaklingar geta búið sér til prófíl, átt samskipti við vini og fjölskyldu, deilt myndum og upplýsingum, spilað leiki og átt samræður í gegnum spjallforrit. Unglingsárin eru viðkvæmt tímabil þar sem unglingar eru næmir fyrir ýmsum félagslegum áhrifum og þess vegna er mikilvægt að skoða hver áhrifin eru af notkun samfélagsmiðla. Spurningalisti frá Rannsóknum og greiningu úr könnuninni Ungt fólk á Íslandi 2013 var notaður við gerð rannsóknarinnar. Valin voru svör 2.070 þátttakenda af tilviljun úr heildarþýði 11.116 framhaldsskólanema. Meirihluti þátttakenda voru á aldrinum 16 ára til 19 ára. Helstu niðurstöður rannsóknarinnar bentu til þess að unglingar sem nota samfélagsmiðla oftar verða fyrir neikvæðum áhrifum af notkuninni (bæði andleg og líkamleg líðan), þar að auki hefur notkun óbein ...